Family Intervention for Obese/Overweight Children Using Portion Control Strategy (FOCUS) for Weight Control - Josephine Ho MD; Sue D. Pedersen MD; Heidi Virtanen BSc; Alberto Nettel-Aguirre PhD; Carol Huang MD, PhD (SAGE Publishing, 2016)
Nutritional counseling for children with obesity is an important component of management. This randomized controlled trial was conducted to compare change in body mass index (BMI) z score after 6 months. Children 8 to 16 years with a BMI greater than the 85th percentile were randomized to standard of care nutrition counseling versus intervention with standard nutrition counseling including portion control tool training for the family. Measures were completed at baseline, 3 months, and 6 months. Fifty-one children were randomized to control and 48 to intervention. Mean age was 11 years (SD = 2.2). Mean BMI z score was 2.7 (SD = 0.4). Forty-five percent were male (n = 45). Follow-up at 6 months was 73.7% (73/99). Although no differences were seen between the groups, there was a significant decrease in BMI z score between baseline and 6 months within each group.